An evaluation tool for sustainable new product development using analytic hierarchy process approach. (2017) - Biju, P.L.; Shalij, P.R.; Prabhushankar, G.V.
Inclusion of sustainability aspects in the very beginning of product development has emerged as an integral part of design process in recent years. Manufacturing organisations are striving to satisfy sustainability requirements (SRs) in their products not only to improve brand value but also as a social commitment towards the future generation. This perspective has urged researchers to develop tools to satisfy SRs in the early stages of product development. In this paper, a tool 'sustainable path modelling (SPM)' has been proposed to identify most suitable options in different stages of product development by evaluating SRs and customer requirements (CRs) separately by applying analytic hierarchy process (AHP). A case study has been conducted to assess and validate the efficiency of the proposed methodology.